Discovery of a Multinary Noble Metal–Free Oxygen Reduction Catalyst. Issue 34 (21st October 2018) - Löffler, Tobias; Meyer, Hajo; Savan, Alan; Wilde, Patrick; Garzón Manjón, Alba; Chen, Yen‐Ting; Ventosa, Edgar; Scheu, Christina; Ludwig, Alfred; Schuhmann, Wolfgang
Abstract: In the endeavor of discovering new noble metal–free electrocatalysts for the oxygen reduction reaction, noble metal–free multinary transition metal nanoparticle libraries are investigated. The complexity of such multiple principal element alloys provides access to a large variety of different elemental compositions, each with potentially unique properties. The strategy for efficient identification of novel electrocatalytically active systems comprises combinatorial co‐sputtering into an ionic liquid followed by potential‐assisted immobilization of the formed nanoparticles at a microelectrode which allows the evaluation of their intrinsic electrocatalytic activity in alkaline media. A surprisingly high intrinsic activity is found for the system Cr–Mn–Fe–Co–Ni, which is at least comparable to Pt under the same conditions, an unexpected result based on the typical properties of its constituents. Systematic removal of each element from the quinary alloy system yields a significant drop in activity for all quaternary alloys, indicating the importance of the synergistic combination of all five elements, likely due to formation of a single solid solution phase with altered properties which enables the limitations of the single elements to be overcome. Multinary transition metal alloys as a novel material class in electrocatalysis with basically unlimited possibilities for catalyst design, targeting the replacement of noble metal–based materials, are suggested. Abstract : The quinary high entropy alloy Cr–Mn–Fe–Co–Ni shows intrinsic oxygen reduction reaction activity which can compete with state‑of‑the‑art Pt nanoparticles. All subsystems show a significant drop in activity, proving the relevance of suitable interactions of specific elements forming new active sites within the formed single solid solution phase. Following this methodology, activity is not limited by the properties of the single contributing elements.